Numerical Analysis for un-baffled Mixing Tank Agitated by Two Types of Impellers (Journal of University of Babylon for Engineering Sciences, 2018)
The effect of impeller flow type and rotation speed on the fluid in mixing tank design under standard configurations investigated to analyses the fluid velocity, turbulent intensity and path lines. In this theoretical study, the fluid motion inside the mixing tank was investigated by solving Navier-Stokes equation and standard k-ε turbulent model in 3-dimensions, for incompressible and turbulent flow. Two types of flow with three types of impellers were investigated, axial-flow with (Lightnin200 and generic impellers) and radial-flow with (Rushton turbine). All impellers evaluated under rotation velocity variation between 10 – 115 rpm. The results showed a direct proportional relationship between the impeller and turbine rotation speed with the fluid velocity in mixing vessel. Also, this case matches with the turbulent intensity and path lines.